LEGAL PREVENTIVE STRATEGIES FOR PREVENTING CONFLICT IN THE EDUCATIONAL PROCESS OF STUDENTS - Ibragimov Shukhrat Isroilovich (The Conference Hub, 2025)
Legal prevention strategies for preventing conflicts in the educational process among students are important in maintaining order in the educational environment and ensuring social harmony. These strategies are aimed at developing legal awareness among students, using constructive approaches to resolving conflicts, and increasing legal culture. Through legal consultations, trainings, and prevention programs in educational institutions, students are taught important methods of effective conflict resolution. Thus, these strategies serve to strengthen social stability in society.
Keywords: education, process, conflict, law, prevention, strategy, environment.